The Digital Divide: Determinants and Policies with Special Reference to Asia - Quibria, M. G. (Institutional Knowledge at Singapore Management University, 2003)
Access to the new information and communication technologies (ICT) remains extremely unequally distributed across and within societies. While there have been a good deal of popular discussions about this digital divide, not much is known about the quantitative significance of its various determinants. By undertaking a set of cross-country regressions, the paper finds that income, education, and infrastructure play a critical role in shaping the divide. Based on this analysis, the paper also offers some policy suggestions as to how to promote a wider diffusion of ICT in poorer societies.